Open reduction and internal fixation of mandibular condylar fractures: A national inpatient sample analysis, 2005–2014. Issue 37 (September 2019) - Kuang, Shi-Jun; He, Yi-Qing; Zheng, You-Hua; Zhang, Zhi-Guang
Abstract : Abstract: The purpose of this study was to compare outcomes of open reduction and internal fixation (ORIF) versus closed reduction (CR) for mandibular condylar fractures. Patients included in the National Inpatient Sample (NIS) database (2005–2014) who were admitted to the hospital for unilateral mandibular condylar fracture were included in the analysis. Patient characteristics and clinical outcomes were compared between those who received ORIF and those receiving CR. Logistic regression analysis was performed to estimate odds ratios (ORs) for each aspect of the main observed events. NIS data of 12, 303 patients who underwent ORIF and 4310 patients who underwent CR were analyzed. Compared to CR, ORIF had an increased risk of longer hospital stay (adjusted OR [aOR] = 1.78, 95% confidence intervals [CIs] = 1.51–2.09), higher total medical cost (aOR = 2.57, 95% CI = 2.17–3.05), and hematoma development (aOR = 10.66, 95% CI = 1.43–75.59), but had a lower risk of having wound complications (aOR = 0.86, 95% CI = 0.79–0.93). Patients with mandibular condylar fractures who receive ORIF have greater risk of having an extended hospital stay, higher total medical costs, and hematoma development but lower risk of experiencing wound complications compared to those who receive CR.